1996
DOI: 10.1063/1.118021
|View full text |Cite
|
Sign up to set email alerts
|

Site-specific reaction kinetics for gallium arsenide metalorganic vapor-phase epitaxy

Abstract: We have developed a kinetic model for arsine decomposition on GaAs(001) that accounts for the effect of the surface reconstructions on the rates of As4 and As2 desorption. The main assumption of the model is that As2 desorbs more slowly from Ga sites than from As sites. The model accurately simulates the temperature-programmed desorption of arsenic from GaAs(001). In addition, it reveals how the As coverage and the As2 and As4 production rates depend on the conditions employed during GaAs metalorganic vapor-ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…One of the goals of scientists working in this field is to develop detailed numerical models that capture the coupled transport phenomena and reaction kinetics of this process. [2][3][4][5] These models could then be used to optimize the reactors for the growth of devices. Studies of indium phosphide MOVPE have found that at 500-700°C, the deposition rate is determined by the mass transfer rate of the group III precursor to the crystal surface.…”
Section: ͓S0003-6951͑99͒02631-5͔mentioning
confidence: 99%
“…One of the goals of scientists working in this field is to develop detailed numerical models that capture the coupled transport phenomena and reaction kinetics of this process. [2][3][4][5] These models could then be used to optimize the reactors for the growth of devices. Studies of indium phosphide MOVPE have found that at 500-700°C, the deposition rate is determined by the mass transfer rate of the group III precursor to the crystal surface.…”
Section: ͓S0003-6951͑99͒02631-5͔mentioning
confidence: 99%
“…For example, the emission intensity of long wavelength InGaAsP/InP lasers depends highly on the interface abruptness during epitaxial growth [6]. The most important factors influencing this abruptness is the mass transport in the boundary layer coupled with the chemical reactions taking place on the film surface [6,7]. A better understanding of the heterogeneous reaction chemistry could lead to further improvements in the MOCVD process.…”
Section: Introductionmentioning
confidence: 99%
“…The film surface plays a crucial role in this process, because it mediates the decomposition of the group III and group V reagents. [4][5][6][7][8][9][10][11][12][13] It is essential to understand the heterogeneous decomposition reactions because they affect the growth rate, film composition, film morphology, and dopant profiles, all of which impact device performance.…”
Section: Introductionmentioning
confidence: 99%